(untitled) (Marketing Journal, 2026)
Abstract This article provides a scientific assessment of the relationship between investment inflows and economic growth in Uzbekistan. The relevance of the study is explained by the need to determine the impact of increasing investment volumes on the growth rate of gross domestic product. The research methodology is based on statistical data analysis, econometric methods, regression modeling, and comparative analysis. The results reveal a positive and statistically significant relationship between investment inflows and economic growth. In particular, foreign direct investment is identified as a key factor accelerating economic growth. The author proposes practical recommendations aimed at improving investment policy and enhancing the investment climate. Keywords: investment inflows, economic growth, gross domestic product, foreign direct investment, investment policy, statistical analysis.